APLIKASI ‘GUESSING GAMES’ UNTUK MENINGKATKAN PRESTASI SISWA DALAM SPEAKING BAGI SISWA SD KELAS 2 - Veronika Unun Pratiwi; Mas Sulis Setiyono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
English is the international language used until now. Because of the importance of the use of English, Indonesian government makes English as a foreign language that was first used (Department of Education, 1981). English began to be taught in Indonesian since the primary school level. Nevertheless, English is only used as an additional subjects or entry into local charge although simple in its early stages as introduction course. This study was conducted to determine whether the application of 'Guessing Games' in the teaching of 'speaking' in second Class at SDN Jombor 1, Sukoharjo can improve student achievement, student interest and motivation of students to the lesson. Based on the research focus on this type of research include descriptive qualitative research. The subject of this study is the second grade students of SDN 01 Jombor Sukoharjo. Data collection techniques to collect data before and after the assessment of such things as the following indispensable namely: interviews, observation, Implementation of Guessing games in learning, and methods of documentation in the form of recording applications of Guessing Game. Based on the results of the study can be concluded as follows; interesting technique can improve the performance of students in learning English since elementary school. This can be seen through the observation of teaching and learning activities in the classroom, the results of interviews and visits from post test results or the value of increased student learning. By using guessing games in teaching speaking, interest and motivation of students to talk can rise well, they are also active in the classroom, in the sense of a positive active involved in learning activities.Keywords: speaking, motivasi, guesing games,